1998
DOI: 10.1144/gsl.sp.1998.130.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Water transport through the unsaturated zone of the Middle Chalk: a case study from Fleam Dyke lysimeter

Abstract: The role of fractures in transporting water in the unsaturated zone of the Chalk has been a source of controversy for many years. There is clearly a potential for fractures to transport water and contaminants rapidly to the saturated zone, although direct observations are rare. The evidence from well hydrographs, solute profiles and soil water measurements is ambiguous concerning the importance of by-pass flow. This paper examines drainage data from several years’ operation of a 5 m cube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…A rather low value that is sensitive to K C was found when calibrating only by discharge operations, indicating some interactions of K C with other model parameters (Saltelli et al, 2008). This is in accordance with the findings by Jones and Cooper (1998) as well as by Reeves (1979), who reported 30 and 10-20 % of the recharge occurring through (macro-) fissures in Chalk catchments. Although groundwater flow in the chalk is dominated by the matrix, given antecedent wet conditions, fracture flow can increase significantly (Lee et al, 2006;Ireson and Butler, 2011;Butler et al, 2012).…”
Section: Reliability Of the Simulationssupporting
confidence: 90%
“…A rather low value that is sensitive to K C was found when calibrating only by discharge operations, indicating some interactions of K C with other model parameters (Saltelli et al, 2008). This is in accordance with the findings by Jones and Cooper (1998) as well as by Reeves (1979), who reported 30 and 10-20 % of the recharge occurring through (macro-) fissures in Chalk catchments. Although groundwater flow in the chalk is dominated by the matrix, given antecedent wet conditions, fracture flow can increase significantly (Lee et al, 2006;Ireson and Butler, 2011;Butler et al, 2012).…”
Section: Reliability Of the Simulationssupporting
confidence: 90%
“…At Fleam Dyke on the Cambridgeshire Middle Chalk, fissure flow was observed to occur at pore pressures greater than À5 kPa in the winter months (Jones and Cooper, 1998). Lysimeter and soil water observations indicate that approximately 30% of flow occurred through fissures throughout the year, and that during the winter months (when no soil moisture deficit was present) 50% of flow occurred through fissures.…”
Section: Previous Work Recharge Pathways and Timingmentioning
confidence: 96%
“…Any remaining recharge and its associated nitrate was bypassed directly to the water table. This idea is based on the hydraulic conductivity relationships observed by Wellings (1984), Hodnett and Bell (1990), Cooper et al (1990), Gardner et al (1990) and Jones and Cooper (1998). Andrews et al (1997) describe their model output as comparing well with observed solute profiles.…”
Section: History Of Chalk Unsaturated Zone Modelsmentioning
confidence: 99%